Migration Potential of Hungarian Healthcare Professionals: Dynamics of Attraction and Repulsion (European Journal of Mental Health, 2009)
The reason why the migration of healthcare professionals has not been described and analyzed yet in Hungary can obviously be found in the authenticity and the lack of this of the Hungarian society. There are several theoretical approaches to the migration processes. Each and every one of them analyzes and defines migration from a different point of view. Our goal was to find out the nature of the migration willingness and activity of Hungarian healthcare specialists. We intended to concentrate primarily on the sociological, cultural-anthropological and social-psychological aspects of this complex phenomenon. This sub-cultural phenomenon can be derived form numerous factors: (a) the family background of Hungarian healthcare specialists, (b) their typical, modal system of values when choosing a profession, (c) the fact that they are typically women, (d) the lack of former experience and knowledge of inspirations in mobility. At the Semmelweis University Faculty of Health Sciences we have already carried out several research projects and their synthesis might lead to the description of the migration trends of healthcare specialists. Four years ago, when we did a study about migration to work abroad, the number of those who predicted leaving the country for sure was the same as today. But the number of those who rejected the whole idea was far higher than nowadays. At that time 20% of healthcare specialists considered a career like this impossible, while now their number is less than 5%. When taking into consideration the fact that the recruiting processes are far more intensive and organized than they used to be, we can expect that a larger number of people can be convinced than ever before. However, the migration intentions are not definite, homogenous or final. The interventions, aiming to keep healthcare specialists in Hungary, still have a chance.